Shopping Center Industry Internationalization with a Focus on Key Resources and Direct Investment: The Case of a Chilean Company in Mexico - Riquelme, Humberto; Bobek, Vito; Horvat, Tatjana (Naše gospodarstvo/Our economy, 2021)
The shopping center sector has been growing steadily over the last years in Latin America. Many countries such as Chile, Mexico, and Brazil lead the indus- try in the region, with so many projects still under development and different companies with international expansion perspectives in their portfolio. The pur- pose of this paper is to identify which are the most recommendable entry mode strategies for Latin American countries and which are the essential resources and capabilities that a shopping center company needs to develop to increase the likelihood of success in the sector. Thus, different factors, such as political, economic, and social factors, which impact the industry operation, are analyzed to create a high-level overview of this industry's most important subjects. For this purpose, primary and secondary data are used, based on a literature review and an empirical qualitative study, giving information of the Chilean Commer- cial Real Estate company, and interviewing its top managers. Thereby, the results lead to an entry strategy proposal into the Mexican market, identifying the most important shopping centers in the country, the main actors, and the best oppor- tunities to enter.